Ionic ratios as markers of interactions between surface water and aquifer in the Quarenta Stream, in Manaus-AM - Lages, Anderson da Silva (2023)
The city of Manaus has numerous bodies of water called igarapés (canoe path – from Tupi) and this is due to the proximity of the water table to the surface, the climatological conditions and the geomorphology of the region. It is known that the city of Manaus underwent an intense and vertiginous process of urbanization, associated with a great polluting pressure on water resources, not only surface water bodies, but also the aquifer. Ionic ratios are ways of establishing similarities in geological environments and show how distinct environments with similar geochemistry can exist. However, similar chemical aspects do not always characterize natural conditions and may represent anthropogenic influence. Therefore, this study aimed to evaluate the ionic ratios of Mg/Na - Ca/Na, HCO3/Na - Ca/Na and Na/Cl x electrical conductivity, based on a monitoring of these variables, which lasted from June 2021 to May 2022, in the Educandos Watershed, in Manaus, associating the study between surface water and groundwater. The results suggested that there is similarity between the aquifer and the igarapé in 2/3 of the groundwater samples, which may be a strong indication of an interaction between the aquifer and surface water, possibly in an infiltration in the igarapé - aquifer sense.